Periodic solutions for a higher-order parabolic equation set on a singular domain in R^{N+1} - B. Chaouchi, M. Kostic, D. Velinov (My University, 2022)
The present work is devoted to the study of a higher-order parabolic equation set on a singular domain in R^{N+1}. The existence and uniqueness of a periodic strict solution are discussed in the framework of Holder spaces. The techniques used here are essentially based on the Dunford functional calculus and the methods applied in [1] and [2].
Keywords: abstract differential equations, periodic boundary conditions, Holder spaces